Spelt in Diversified and Spelt-Based Crop Rotations: Grain Yield and Technological and Nutritional Quality - Maria Wanic; Magdalena Jastrzębska; Marta K. Kostrzewska; Mariola Parzonka (Agriculture, 2024)
A properly designed crop rotation contributes to the equilibrium of the agro-ecosystem and the volume and quality of the yield. The cultivation of spelt in crop rotations enriches its biodiversity and provides grains with many different types of nutritional value. The aim of this current study was to investigate how the distribution of winter spelt in different positions and after different forecrops in four-field crop rotations would affect the technological quality of the grain, the nutrient content of the grain, and the grain yield. A 6-year field experiment, designed in a randomised block, was conducted from 2012 to 2018 in north-eastern Poland (53°35′47″ N, 19°51′20″ E). This study provides the results from a 6-year (2013–2018) field experiment. The spelt was cultivated in four crop rotations: CR1—winter rape + catch crop (blue tansy), spring barley, field pea and winter spelt; CR2,—winter rape, winter spelt + catch crop (blue tansy), field pea and winter spelt; CR3—winter rape + catch crop (blue tansy), field pea, winter spelt and winter spelt; and CR4—winter rape, winter spelt + catch crop (blue tansy), spring barley and winter spelt. This study evaluated grain yield and the following grain parameters: the total protein, wet gluten and starch contents, the Zeleny index, the falling number, the weight of 1000 grains, the N, P, K, Mg, Ca, Cu, Fe, Zn and Mn contents, and the grain yield. The results were assessed at the significance level p < 0.05. It was demonstrated that the cultivation of spelt in all four crop rotations after winter rape and after field pea was characterised by higher protein and wet gluten contents, Zeleny index value and falling number, a greater weight of 1000 grains, higher N, P, Fe and Zn contents, and greater grain yield than those harvested from the crop rotations CR3 and CR4 after spelt and after barley. It was demonstrated that the cultivation of spelt in crop rotations CR3 and CR4, in succession after spelt and after barley, caused deterioration in grain quality (lower protein and gluten contents, a lower Zeleny index value, a lower falling number, and a smaller weight of 1000 grains, and the N, P, Fe and Zn contents). In addition, a smaller grain yield was obtained from these crop rotation fields. Regardless of the type of crop rotation, the cultivation of spelt after winter rape and after pea produced a high yield and a good quality yield of this cereal. Due to the lower yield of grain and its lower quality, it is not recommended that winter spelt is grown after each other or after spring barley.